Odpowiedź :
Odpowiedź:
a) 3x - 4= 5x - 6
6-4= 5x - 3x
2= 2x | :2
1=x
b) 2x - 8 + 3x - 2 = 6 + x
2x + 3x - x = 8 + 2 + 6
4x = 16 | : 4
x= 4
c) -5x + 4 = 3 - 2(x + 4)
-5x + 4 = 3 - 2x -8
4 - 3 + 8 = 5x - 2x
9 = 3x | : 3
3 = x
d) 7( x + 2) - x = 5(x - 2)
7x + 14 - x = 5x - 10
7x - x - 5x = - 10 - 14
x = -24
e) -(x+1) + 8x = 5x - 9
-x - 1 + 8x = 5x - 9
-x + 8x - 5x = 1 - 9
2x = -8 | : 2
x = -4
a.
3x - 4 = 5x - 6
3x - 5x = -6 + 4
-2x = -2 | : -2
x = 1
b.
2x - 8 + 3x - 2 = 6 + x
5x - 10 = 6 + x
5x - x = 6 + 10
4x = 16 | :4
x = 4
c.
-5x + 4 = 3 - 2 (x + 4)
-5x - 4 = 3 - 2x - 8
-5x - 4 = -2x - 5
-5x + 2x = -5 + 4
-3x = -1 | :-3
x = 1/3
d.
7 (x + 2) - x = 5 (x - 2)
7x + 14 - x = 5x - 10
6x + 14 = 5x - 10
6x - 5x = -10 - 14
x = -24
e.
-(x + 1) + 8x = 5x - 9
-x - 1 + 8x = 5x - 9
7x - 1 = 5x - 9
7x - 5x = -9 + 1
2x = -8 | :2
x = -4
Mam nadzieje, ze pomogłam :))